The influences of personality and knowledge on safety-related behaviour among climbers. Issue 23 (2nd December 2021) - Esfahani, Mahdi; Khoo, Selina; Musa, Ghazali; Heydari, Reza; Keshtidar, Mohammad
ABSTRACT: Research on safety-related behaviour among mountaineers remains scarce. Using the theory of planned behaviour, this study investigates the relationships between personality and components of this theory with safety-related behaviour, among climbers on Mount Kinabalu, Borneo. A total of 750 climbers completed questionnaires and the data were analysed using structural equation modelling. Climbers on Mount Kinabalu possess the highest personality dimension of openness to experience, followed by agreeableness, extraversion, conscientiousness and neuroticism. The level of safety-related behaviour on the mountain was moderate. Personality influences climbers' safety-related behaviour both directly and indirectly through knowledge as a mediator factor. Based on the findings, we propose some managerial and marketing implications.